Analysis of Influence of Social Media on Water Resource Conservation under Stewardship of Lake Victoria Basin Water Board in Mwanza City, Tanzania - Sostheness Abeidinego Mganga; Peter C. Mataba; Sakina Faru (Technium Social Sciences Journal, 2026)
Purpose: This study explored how Lake Victoria Basin Water Board’s (LVBWB) social media practices influence public awareness, perceptions and conservation-related intentions among stakeholders in Mwanza City, Tanzania. The study interrogated platform usage, content characteristics, engagement dynamics and institutional practices to understand why digital visibility often fails to translate into sustained conservation behavior. Methodology: Purposive qualitative case study design was employed. Data sources included documentary review of LVBWB social media outputs and institutional materials (March–September 2025), non-participant observation at two outreach events and Key Informant Interviews from 14 purposively sampled key-informant interviewees with LVBWB staff, community leaders, fishing community representatives, youth group leaders and Non-Governmental Organisation environmental actors. Then data were grouped into themes and subjected to content analysis. Anonymized illustrative excerpts are included. Findings: Five interrelated themes emerged: (1) episodic and event-driven posting that produces transient salience rather than cumulative agenda-setting; (2) language and tone barriers, where formal or technical citations limit accessibility; (3) visibility without dialogue, where “likes” and impressions do not equate to participation or ownership; (4) local intermediaries as trust multipliers, with community leaders and youth champions essential for mobilization; and (5) institutional constraints (approval bottlenecks, limited communication capacity, and absence of formal feedback protocols) that inhibit two-way engagement. The study proposes a pragmatic hybrid communication model combining sustained social media practice, Kiswahili-first messaging, local co-creation and institutionalized feedback to bridge awareness–action gap. Unique contribution: This paper provides contextually grounded, actionable guidance for LVBWB and similar institutions in East Africa by integrating TAM-informed adoption insights with Public Relations and social marketing principles, while retaining strict fidelity to qualitative evidence.